1982
DOI: 10.1159/000238135
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Antimicrobial Drugs and Combined Phagocytic/Serum Bactericidal Activity of Defibrinated Human Blood against <i>Serratia marcescens</i>

Abstract: Minimal bactericidal concentrations of the aminoglycoside antibiotics amikacin, gentamicin, and netilmicin killed intraphagolysosomal test bacteria of selected assay strains of Serratia marcescens, though not as efficiently as rifampin. The system employed consisted of 55 vol % of fresh defibrinated human blood treated with 2 mg/ml of phenylbutazone which permitted ingestion of bacteria, but selectively inhibited microbicidal activity of the peripheral blood leukocytes. Extraphagocytic bacteria were killed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 13 publications
3
31
0
Order By: Relevance
“…Of par ticular interest was the finding that of the four fluoroquinolones examined, cipro floxacin yielded the most rapid and po tent intraphagocytic bactericidal activity against our control strain of P. aeruginosa. And as noted before in our Serratia marcescens system [36], p-lactam and amino glycoside antibiotics were only feebly or moderately active ingested P. aeruginosa cells; however, polymyxin B occupied an intermediate position.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Of par ticular interest was the finding that of the four fluoroquinolones examined, cipro floxacin yielded the most rapid and po tent intraphagocytic bactericidal activity against our control strain of P. aeruginosa. And as noted before in our Serratia marcescens system [36], p-lactam and amino glycoside antibiotics were only feebly or moderately active ingested P. aeruginosa cells; however, polymyxin B occupied an intermediate position.…”
Section: Discussionsupporting
confidence: 82%
“…4, the least blood-susceptible of all strains, was included in all experiments comprising the first two series of com bined human blood-antimicrobial drug assays. As before [36], we chose to perform time-kill curve experiments [8], inasmuch as these permitted evaluation of the bac tericidal activities of drugs or drug combi nations during various points in time over prolonged incubation periods. In addi tion, Moody et al [25] found conventional inoculum time-kill rates at extravascularly achievable antimicrobial drug concentra tions to be a good predictor for the out come of closed-space P. aeruginosa infec tions at locally neutropenic sites in rab bits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations